2020
DOI: 10.1002/agj2.20168
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐risk assessment for winter wheat using long‐term weather data

Abstract: Temperature and water deficit stresses cause large year-to-year yield variability, and matching crop phenology with periods less prone to stresses can improve yield stability. We used 30 years of daily weather data from 69 stations in the U.S. Great Plains to quantify the risk of water deficit and temperature stresses for winter wheat (Triticum aestivum L.) cultivars differing in maturity, and to evaluate whether the selected variables explained variability in yield and area abandonment. Crop phenology was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…Our results also suggested that water deficit stress was rarely a yield‐limiting factor; instead, excessive grain fill precipitation tended to restrict wheat yield for both wheat classes. These findings agree well with a recent climate‐risk assessment for winter wheat in the region (Lollato et al., 2020). This excessive precipitation may contribute to increased incidence and severity of fungal diseases that limit wheat yield (de Oliveira Silva, Slafer, Fritz, & Lollato, 2019; Jaenisch, de Oliveira Silva, DeWolf, Ruiz‐Diaz, & Lollato, 2019; Kelley, 2001; Lollato et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also suggested that water deficit stress was rarely a yield‐limiting factor; instead, excessive grain fill precipitation tended to restrict wheat yield for both wheat classes. These findings agree well with a recent climate‐risk assessment for winter wheat in the region (Lollato et al., 2020). This excessive precipitation may contribute to increased incidence and severity of fungal diseases that limit wheat yield (de Oliveira Silva, Slafer, Fritz, & Lollato, 2019; Jaenisch, de Oliveira Silva, DeWolf, Ruiz‐Diaz, & Lollato, 2019; Kelley, 2001; Lollato et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Two winter wheat genotypes with similar yield performance but contrasting GPC histories, exposed to different N rates and N timings under a range of environments, revealed N management and genotypic opportunities to increase wheat grain yield and GPC simultaneously, disrupting the commonly reported negative relationship between both variables. The range of environmental conditions evaluated is representative of the long‐term weather in the region (Lollato et al., 2020b; Torres, Lollato, & Ochsner, 2013) and the negative yield–GPC relationship is detrimental to global food security (Simmonds et al., 1995), possibly leading to GPC below market standards and influence the value of the wheat grain (Dick, Thompson, Epplin, & Arnall, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the additional N application in our study increased N concentration in the stem and grain for IM relative to the SM ( p < .05 , data not shown), and may explain why the N dilution curve for the IM was above the critical dilution curve of SM (i.e., under luxury consumption of N). This difference among dilution curves for IM as compared to SM also suggests that intensifying management can help to increase crop nutritional status even when water is limited, which is a common yield‐limiting factor in the U.S. southern Great Plains (Lollato et al., 2020). Similar to our findings, Reussi et al.…”
Section: Discussionmentioning
confidence: 99%